Probiotics Reduce Postoperative Infections in Patients Undergoing Colorectal Surgery: A Systematic Review and Meta-Analysis - Peng Cheng Liu; Yu Ke Yan; Yu Jing Ma; Xiang Wen Wang; Jie Geng; Man Cai Wang; Feng Xian Wei; Ya Wu Zhang; Xiao Dong Xu; You Cheng Zhang (Gastroenterology Research and Practice)
Background. We performed this meta-analysis to investigate the efficacy of probiotics on prevention of infection-related complications following colorectal resection. Method. PubMed, EMBASE, Cochrane Library, and the Web of Science were searched up to January 2016. According to the results, only randomized controlled trials that compared the efficacy of probiotics on patients with colorectal resection were included for meta-analysis. Results. Nine studies including a total of 1146 patients met the criteria (556 received multistrain probiotic bacteria, 590 with non-multistrain probiotic bacteria). The combination of multistrain probiotics was beneficial in the reduction of total infections (OR = 0.30, 95%CI: 0.15–0.61, p=0.0009), including surgical site infections (SSI) (OR = 0.48, 95%CI: 0.25–0.89, p=0.02) and nonsurgical site infections (NSSI) (OR = 0.36, 95%CI: 0.23–0.56, p<0.00001). However, there was no significant reduction in total infections (OR = 0.74, 95%CI: 0.50–1.09, p=0.13) or SSI (OR = 0.77, 95%CI: 0.52–1.12, p=0.17) with the application of non-multistrains of probiotics. Conclusion. Combinations of multistrain probiotic bacteria showed promise in preventing the incidence of infections following colorectal surgery. However, the efficacy of one or two strains of probiotics remains undetermined.